2021
DOI: 10.1111/echo.14993
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular functions by speckle‐tracking echocardiography in coarctation patients

Abstract: Coarctation of the aorta (CoA) is a relatively common defect that occurs in the general population at a rate of 0.06%-0.08%, constituting 6%-8% of congenital heart disease. 1,2 CoA can be clinically asymptomatic, or it may present with a shock in infancy and may present with systemic hypertension, intracranial bleeding, and heart failure in adults. 3 Even if CoA is successfully treated, systemic hypertension can lead to the development of late complications such as left ventricular (LV) hypertrophy, heart fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Moreover, several inflammatory substances released from adipocytes, such as resistin have been suggested to contribute toward the adverse effects of obesity on the heart by promoting myocardial hypertrophy and dysfunction 21 . Extensive research has reported that the myocardial strain obtained by two-dimensional speckle tracking imaging can make left ventricular quantization beyond LVEF a better prognostic marker of cardiac events 22 24 . In this study, no significant difference in AAO, LAD, LVEDd, LVEF, A and E/e′ was reported between the thin and thick EAT groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several inflammatory substances released from adipocytes, such as resistin have been suggested to contribute toward the adverse effects of obesity on the heart by promoting myocardial hypertrophy and dysfunction 21 . Extensive research has reported that the myocardial strain obtained by two-dimensional speckle tracking imaging can make left ventricular quantization beyond LVEF a better prognostic marker of cardiac events 22 24 . In this study, no significant difference in AAO, LAD, LVEDd, LVEF, A and E/e′ was reported between the thin and thick EAT groups.…”
Section: Discussionmentioning
confidence: 99%